2019
DOI: 10.1016/j.biortech.2019.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Selective production of volatile fatty acids at different pH in an anaerobic membrane bioreactor

Abstract: This study investigated the production of major volatile fatty acid (VFA) components in an anaerobic membrane bioreactor (AnMBR) to treat low-strength synthetic wastewater. No selective inhibition was applied for methane production and solvent-extraction method was used for VFA extraction. The results showed acetic and propionic acid were the predominant VFA components at pH 7.0 and 6.0 with concentrations of 1.444 ± 0.051 and 0.516 ± 0.032 mili-mol/l respectively. At pH 12.0 isobutyric acid was the major VFA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Research studies have shown that between pH 5.0 and 6.0, the highest overall VFA concentration is observed regardless of the type of which inoculum was used while producing VFA from food waste [64]. However, Khan et al (2019) reported that the highest VFA yield from low-strength synthetic wastewater recorded 48.74 ± 1.5 mg VFA/ 100 mg CODfeed at pH 7.0, whereas Jie et al…”
Section: Vfa Recoverymentioning
confidence: 98%
See 4 more Smart Citations
“…Research studies have shown that between pH 5.0 and 6.0, the highest overall VFA concentration is observed regardless of the type of which inoculum was used while producing VFA from food waste [64]. However, Khan et al (2019) reported that the highest VFA yield from low-strength synthetic wastewater recorded 48.74 ± 1.5 mg VFA/ 100 mg CODfeed at pH 7.0, whereas Jie et al…”
Section: Vfa Recoverymentioning
confidence: 98%
“…The fouling layer can eventually retain VFA inside the anaerobic bioreactor, and make the separation and purification processes even more challenging [38,39]. On this issue, Khan et al (2019) carried out an experiment to produce VFA from low strength synthetic wastewater using a single stage AnMBR [3]. There results showed the highest VFA yield of 48.20 ± 1.21% (mg VFA/mg CODfeed) at HRT lasting 8 hrs.…”
Section: # Insert Table 2 ##mentioning
confidence: 99%
See 3 more Smart Citations